Balloon observation, and instructions on the subject of work in the basket - United States. War Department. Division of Military Aeronautics (Salt Lake City, UT : Project Gutenberg, 2023)
"Balloon Observation, and Instructions on the Subject of Work in the Basket" is a military instruction manual issued by the Division of Military Aeronautics, U.S. Army, in August 1918. This scientific publication, likely written during the late stages of World War I, focuses on the principles and techniques of balloon observation, particularly in the context of artillery support and reconnaissance. The book provides a comprehensive look at how to effectively utilize balloons for military observation tasks, detailing procedures, communication protocols, and the importance of understanding the terrain. The manual is divided into sections that address balloon observation principles, tactical coordination with artillery units, and specific work methods for observers while in the basket. It emphasizes the need for precision in spotting targets and reporting fire, including techniques for orientation, reconnaissance, and the identification of key terrain features. By outlining the relationship between balloon observers and artillery commanders, the text aims to improve the effectiveness of military operations through careful observation and communication. Detailed methodologies are provided for tasks such as marking target locations, assessing artillery impacts, and employing visual aids like maps and photographs to ensure accuracy in observations. (This is an automatically generated summary.)
Release date is 2023-10-23
Aaron Adrignola and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Balloons; Aerial observation (Military science); Military reconnaissance; Aerial reconnaissance